Luigi Einaudi: Selected Political Essays, Volume 3 - Empoli, Domenico da.; Malandrino, Corrado.; Zanone, Valerio. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Luigi Einaudi (1874-1961) was a leading liberal Italian economist, economic historian and political figure: Governor of the Bank of Italy, Minister for the Budget and President of the Italian Republic. He was a prolific writer in all fields and his writings testify to his outstanding contribution to economics during his long career.